Petrology and geochemistry of feldspathic impact‐melt breccia Abar al' Uj 012, the first lunar meteorite from Saudi Arabia. (October 2016) - Mészáros, Marianna; Hofmann, Beda A.; Lanari, Pierre; Korotev, Randy L.; Gnos, Edwin; Greber, Nicolas D.; Leya, Ingo; Greenwood, Richard C.; Jull, A. J. Timothy; Al‐Wagdani, Khalid; Mahjoub, Ayman; Al‐Solami, Abdulaziz A.; et al.
Abstract: Abar al' Uj (AaU) 012 is a clast‐rich, vesicular impact‐melt (IM) breccia, composed of lithic and mineral clasts set in a very fine‐grained and well‐crystallized matrix. It is a typical feldspathic lunar meteorite, most likely originating from the lunar farside. Bulk composition (31.0 wt% Al2 O3, 3.85 wt% FeO) is close to the mean of feldspathic lunar meteorites and Apollo FAN‐suite rocks. The low concentration of incompatible trace elements (0.39 ppm Th, 0.13 ppm U) reflects the absence of a significant KREEP component. Plagioclase is highly anorthitic with a mean of An96.9 Ab3.0 Or0.1 . Bulk rock Mg# is 63 and molar FeO/MnO is 76. The terrestrial age of the meteorite is 33.4 ± 5.2 kyr. AaU 012 contains a ~1.4 × 1.5 mm 2 exotic clast different from the lithic clast population which is dominated by clasts of anorthosite breccias. Bulk composition and presence of relatively large vesicles indicate that the clast was most probably formed by an impact into a precursor having nonmare igneous origin most likely related to the rare alkali‐suite rocks. The IM clast is mainly composed of clinopyroxenes, contains a significant amount of cristobalite (9.0 vol%), and has a microcrystalline mesostasis. Although the clast shows similarities in texture and modal mineral abundances with some Apollo pigeonite basalts, it has lower FeO and higher SiO2 than any mare basalt. It also has higher FeO and lower Al2 O3 than rocks from the FAN‐ or Mg‐suite. Its lower Mg# (59) compared to Mg‐suite rocks also excludes a relationship with these types of lunar material.